1994
DOI: 10.1095/biolreprod51.5.1051
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Follicular Development in Prepubertal Heifers is Influenced by Level of Dietary Energy Intake1

Abstract: Objectives were twofold: 1) to determine the chronology of development of dominant ovarian follicles during the peripubertal period in heifers and 2) to determine whether feeding a diet with low energy content that delays onset of puberty alters chronology of dominant ovarian follicular development in peripubertal heifers. Ten heifers of composite breeding (1/4 Angus, 1/4 Hereford, 1/4 Red Poll, 1/4 Pinzgauer) were randomly assigned, at 8 mo of age, to receive a diet designed to produce 0.9 (n = 5) or 0.3 (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
39
0
10

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 31 publications
7
39
0
10
Order By: Relevance
“…In period 2, significantly different LW gain were achieved in the two groups of heifers: 730 g/day for the restricted group versus 1300 g/day for the overfed group. Such LW gain is close to that observed in French farms (Troccon 1993, Gaboriau 2002) as well as in other studies on heifers (Bergfeld et al 1994, Saumande et al 1998, Carson et al 2000, Armstrong et al 2001, Chelikani et al 2003. The increase from 950 g/day in period 1 to 1300 g/day in period 2 for the overfed group could be due to an improvement of nutritional efficiency during the 4 months of experiment.…”
Section: Growth Rate Body Weight and Bcssupporting
confidence: 90%
“…In period 2, significantly different LW gain were achieved in the two groups of heifers: 730 g/day for the restricted group versus 1300 g/day for the overfed group. Such LW gain is close to that observed in French farms (Troccon 1993, Gaboriau 2002) as well as in other studies on heifers (Bergfeld et al 1994, Saumande et al 1998, Carson et al 2000, Armstrong et al 2001, Chelikani et al 2003. The increase from 950 g/day in period 1 to 1300 g/day in period 2 for the overfed group could be due to an improvement of nutritional efficiency during the 4 months of experiment.…”
Section: Growth Rate Body Weight and Bcssupporting
confidence: 90%
“…The follicular development pattern observed in this study, increasing linearly in time, agrees with Bergfeld et al (1994), who demonstrated a linear increase in the DF maximum diameter of prepubertal heifers approaching puberty and also demonstrated that greater energy accelerated follicular growth. The mechanism by which energy intake infl uences follicle development is not yet fully elucidated.…”
Section: Discussionsupporting
confidence: 90%
“…Sirois and Fortune, 1988;Sartori et al, 2002;Wolfenson et al, 2004). Significantly fewer experiments have been performed on beef heifers (Hooper et al, 1993;Bergfeld et al, 1994;Evans et al, 1994;Gasser et al, 2006) and we found no paper dealing with dual-purpose breeds of cattle. Czech Fleckvieh heifers rank among dual-purpose breeds, reaching puberty at 8-10 months, weighing 340-360 kg at 12 months, and with milk yield of 5 800 kg at the first lactation.…”
mentioning
confidence: 58%
“…There are many factors affecting the reproductive efficiency of heifers, for example body weight (Chebel et al, 2007), metabolic status (Bergfeld et al, 1994;Ferguson, 2005), BCS (Sejrsen et al, 1999), heat stress (Wilson et al, 1998a) and sufficient ovarian activity (Fortune, 1993).…”
mentioning
confidence: 99%